The Quality of Society and Happiness: Fairness, Trust, and Community in China - Knight, J; Gunatilaka, R (Springer, 2024)
Adam Smith argued that ‘moral sentiments’ – the norms, customs and conventions of society - provide a benefit, improving both economic efficiency and well-being. Three important moral sentiments are a perception of fairness, a willingness to trust people, and a sense of community. We analyse representative national socioeconomic surveys of the China Household Income Project (CHIP), containing information that is used to create scores of happiness, fairness, trust, and community for each respondent. Three main hypotheses are tested: that higher reported fairness, higher reported trust, and greater sense of community each raises happiness. Evidence is found for each hypothesis, as well as for related questions, Attempts are made to ascertain whether the associations are causal; some support is found. The evidence is generally consistent with the broader argument that an informal social contract constrains antisocial behaviour and improves wellbeing in ways little studied by economists.